CMET-15. SARCOPENIA INDEPENDENTLY AND STRONGLY PREDICTS SURVIVAL IN PATIENTS UNDERGOING SPINE SURGERY FOR METASTATIC TUMORS. (11th November 2019) - Zakaria, Hesham; Saadeh, Yamaan; Lau, Darryl; Pennington, Zachary; Ahmed, Ali; Chandra, Ankush; Macki, Mohamed; Lee, Ian; Chou, Dean; Park, Paul; Sciubba, Daniel; Chang, Victor
Abstract: INTRODUCTION: Predicting survival and surgical morbidity in patients with spinal metastases would help guide clinical decision making and stratify treatments between surgical intervention and palliative care. This multi-center retrospective cohort study evaluates whether the frailty/sarcopenia paradigm, as measured by psoas size, is predictive of survival in patients undergoing surgery for spinal metastasis. METHODS: 271 patients from four institutes who had undergone surgery for spinal metastasis were identified. Morphometric measurements were taken of the psoas muscle at the L4 vertebral level < 200d from surgery. Mortality hazard ratios were calculated using multivariate analysis, with variables included from past medical history, type and extent of tumor spread, type and intensity of surgery, and postoperative chemotherapy or radiation. RESULTS: Psoas size was predictive of overall mortality; patients in the smallest tertile had shorter overall survival compared to the middle (OR 0.52, p< 0.001) and largest tertile (OR 0.45, p< 0.001). Psoas size predicted overall mortality more strongly than Tokuhashi score (OR 0.91, p= 0.010), Tomita score (OR 1.07, p= 0.04), and KPS (OR 0.99, p= 0.58). Psoas size was also predictive of 90-day survival; patients in the smallest tertile had shorter 90-day survival compared to the middle (OR 0.24, p= 0.003) and largest tertile (OR 0.16, p= 0.001). Psoas size predicted 90-day mortality more strongly than Tokuhashi score (OR 0.73, p= 0.002), Tomita score (OR 1.00, p= 0.92), and KPS (OR 0.98, p= 0.39). CONCLUSION: In patients undergoing surgery for spine metastases, psoas size as a surrogate for frailty/sarcopenia predicts 90-day and overall mortality, independent of demographical, functional, oncological, and surgical characteristics. The sarcopenia/frailty paradigm is a stronger predictor of survival at these time points than the Tokuhashi score, Tomita score, and KPS. Psoas size can be used in clinical decision-making to select which patients with metastatic spine tumors are appropriate surgical candidates.